Single-cell analysis of T lymphocytes infiltrating colorectal carcinoma: the dilemma of specificity - Manuela Lizarralde-Guerrero; Laura Zucaro; Guido Kroemer; Jonathan G. Pol (OncoImmunology)
Advances in single-cell RNA and T cell receptor (TCR) sequencing allow to study the specificity and functionality of tumor-infiltrating T lymphocytes. A recent study unravels fundamental differences between microsatellite-instable (MSI) colorectal cancers, in which T cells tend to be tumor-specific, and microsatellite-stable (MSS) cancers, in which T cells exhibit bystander features.